EFFECT OF GLUCOSE ON THE RESPONSE PAIN BABY IN PUSKESMAS GAMPING II SLEMAN YOGYAKARTA - Abdul Ghofur; Ida Mardalena (Universitas Muhammadiyah Semarang, 2014)
Background. Evidence suggests that infants feel pain, and painful experiences may lead to subsequent increased pain sensitivity. Owing to concerns regarding the potential adverse effects of pharmacological interventions in newborns, effective alternatives for pain control are being sought. Pain response in infants perpapar painful invasive procedures become an important issue and needs to be given a way out, so that did not hamper the future growth and development. Efforts non-pharmacological form of glucose is a supplement that can reduce the pain response in infants. Glucose is also easy to get in the domestic order in Indonesia.This study aims to determine the effect of glucose on pain response in infants who performed immunization injection Methods. This research method is quasi elsperiment by design